Predators of 'Phyllocnistis citrella 'Stainton (Lepidoptera: Gracillariidae) on citrus in Spain: role of lacewings and ants Importance of beneficials. "Pesticides and beneficials organisms" - Jaques, Josep A.; Urbaneja, Alberto (2017)
Spain is the largest producer of citrus for the fresh market worldwide (FAO, 2003). Many potential pests occurring in this crop are kept under excellent biological control by their natural enemies (Ripollés et al., 1995). Most of these natural enemies are specialists [e.g. Rodolia cardinalis Mulsant (Coleoptera: Coccinellidae)] and their role is widely recognized among citrus entomologists. Because of this status, investigations on side effects of pesticides on these species are routinely undertaken (Jacas & García Marí, 2001). Nevertheless, the invasion of Spanish citrus orchards by the citrus leafminer [Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae)] during the last decade of the twentieth century gave us the chance to quantify the contribution of opportunistic parasitoids and predators to mortality inflicted by natural enemies (both indigenous and exotic) on this pest. Recent studies where mortality caused by natural enemies took into account the effects of predation, parasitism and feeding punctures pointed at predation as the most important mortality factor overall (Pomerincke, 1999; Urbaneja et al., 2000a). In Spain, predation represented up to 60 % of total mortality caused by natural enemies (Urbaneja et al., 2000a). Nevertheless, it was not possible to relate predation rates to P. citrella numbers along the season. It appeared that generalist predators were not responding to variation in the density of P. citrella but to flushing. Predation rates were significantly related to densities of young receptive flushes, and this might be related to continuous availability of preferential hosts, such as aphids. Therefore, it was concluded from that study that generalist predators feeding on aphids, such as lacewings, and aphid-mutualists, such as ants, which also feed on citrus leafminer, were probably responsible for observed predation rates. For this reason, a study aimed at quantifying the role of Chrysoperla carnea Stephens (Neuroptera: Chrysopidae) and ants (Hymenoptera: Formicidae) as predators of P. citrella was undertaken.